Jewish Holidays from a Torah Perspective - Mariana Hartman (European Scientific Journal, ESJ, 2019)
Religious-legal relations is a unique in its kind component of any society. The relationship between religion and law is always reflected through the normative and institutional component of the legal system, and is also characterized by peculiar properties which are exclusively inherent for the Jewish society. The Jewish society is a vivid example of the fact when religious holidays give a special colouring to the Jewish religious-legal ideology and enhance the contrast in respect to other religious-legal systems of the world. Such identity is preceded by the history of self-determination of the Jewish people, the genesis of the formation and evolution of the legal system, as well as the type of the legal ideology of Jewish society. All of this collectively forms the general understanding of what constitutes the Jewish holidays and what content and idea is put into each of them. The object of the research is the social relations of the Jewish people, that reflect the order of keeping and celebrating the Jewish holidays established and regulated by the Torah. The article is devoted to the study of the genesis and process of the establishment of Jewish holidays as one of the components of the Jewish legal tradition with centuries-old history. Taking into account the object ofscientific research, the author has used general scientific and special-scientific methods. The main method which has been used in the research is – discrete method, with the help of which the genesis of Jewish holidays is revealed through the prism of Torah. The author has partially used the historical, system, comparative legal, hermeneutical methods and method of critical analysis. The historical method used is especially of great current interest, as far as the study of origin and formation of Jewish holidays requires a retrospective analysis and identification of the relevant developmental patterns. Also system method has been used - the application of it is due to the necessity of systematization of religious holidays. Was to be used a comparative legal method, with the help of which the Jewish days-off and holidays are compared with each other and partially with the holidays of other types of legal systems. The hermeneutic method is specified by the necessity of understanding and knowledge of the texts of Jewish laws - the Tories, the Talmud, and other Halachic sources of law. The use of the method of critical analysis as one of the basic in historical-legal studies had contributed to the analysis of scientific literature, which was used as the basis for the study. On the basis of the formal criterion, the content of Jewish holidays, which was initiated by the rules of the Writen Torah, is still open today. The peculiarity of Jewish holidays is illuminated through the prism of Halachic norms, including the Writen Torah, the Talmud, and the Halachic sources of the post-Talmudist period. Analyzing sources of Jewish law it was found that, taking into account the long history of Jewish law-making, the legal approach of halachists to the perception of Jewish holidays evolved and changed. This was due to the needs of the time and circumstances in which the Jewish people appeared. The author comes to the conclusion that the place devoted to religious holidays in the Jewish legal ideology is extremely important, confirmation of which is the preservation of the religious-legal values defined by Torah for more than 4 thousand years and their transformation into the religious legal system of the modern state of Israel.